2015
DOI: 10.31055/1851.2372.v50.n3.12526
|View full text |Cite
|
Sign up to set email alerts
|

Cambios climáticos en las sierras de Córdoba (Argentina) durante el holoceno. Aportes a las reconstrucciones climáticas a través del análisis de silicofitolitos del sitio arqueológico El Alto 3.

Abstract: El análisis de silicofitolitos es una herramienta cada vez más utilizada para la reconstrucción paleoclimática. Sin embargo, en Córdoba estas reconstrucciones se han realizado con otras técnicas. En este trabajo nos propusimos calcular los índices climáticos internacionales a partir de los silicofitolitos, validar dichos índices utilizando la distribución de la vegetación y clima actual de las sierras, y presentar la primera reconstrucción paleoclimática a través de silicofitolitos para el sitio arqueológico m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 44 publications
(53 reference statements)
0
8
0
1
Order By: Relevance
“…In the study area, mean annual temperature vary from an average of 16.5 °C below 900 m a. s. l. to 7.5 °C at the highest elevation in Mt Champaquí, with potential evapotranspiration following a similar decreasing trend (Table 2) (Marcora et al 2008;Fick and Hijmans 2017). In the upper portion of the study area, mean annual precipitation reaches more than 900 mm, whereas at low elevations there is a regional rainfall gradient from east (annual rainfall 700-800 mm) to west (annual rainfall 500-600 mm), with most rainfall being concentrated in the warmest months (Colladon and Pazos 2014;Giorgis et al 2015;Colladon 2018) (Table 2). Relatively high temperatures occur in August and September, after some months of very low rainfall, favoring seasonal fires in late winter and early spring.…”
Section: Study Areamentioning
confidence: 66%
See 1 more Smart Citation
“…In the study area, mean annual temperature vary from an average of 16.5 °C below 900 m a. s. l. to 7.5 °C at the highest elevation in Mt Champaquí, with potential evapotranspiration following a similar decreasing trend (Table 2) (Marcora et al 2008;Fick and Hijmans 2017). In the upper portion of the study area, mean annual precipitation reaches more than 900 mm, whereas at low elevations there is a regional rainfall gradient from east (annual rainfall 700-800 mm) to west (annual rainfall 500-600 mm), with most rainfall being concentrated in the warmest months (Colladon and Pazos 2014;Giorgis et al 2015;Colladon 2018) (Table 2). Relatively high temperatures occur in August and September, after some months of very low rainfall, favoring seasonal fires in late winter and early spring.…”
Section: Study Areamentioning
confidence: 66%
“…As in any typical mountain system, the climate in the Córdoba mountains is largely associated with the elevation gradient, with a minor influence of geographic gradients or other topographic features (Marcora et al 2008;Giorgis et al 2015;Sparacino et al 2019). In the study area, mean annual temperature vary from an average of 16.5 °C below 900 m a. s. l. to 7.5 °C at the highest elevation in Mt Champaquí, with potential evapotranspiration following a similar decreasing trend (Table 2) (Marcora et al 2008;Fick and Hijmans 2017).…”
Section: Study Areamentioning
confidence: 99%
“…Nonetheless, simulations showed that the region could have been almost completely covered by dry forest (Cingolani, Renison, Tecco, Gurvich, & Cabido, 2008). The presence of megaherbivores until the beginning of the Holocene and the arrival of humans around 10,000 years ago suggest that vegetation has a long history of disturbances, such as grazing and fire (Giorgis, Lopez, Rivero, & Cingolani, 2015;Lindskoug & Marconetto, 2014); moreover, domestic European livestock were introduced into these mountains about 400 years ago (Díaz, Acosta, & Cabido, 1994). Accordingly, it is likely that fire frequencies were much lower in the past, allowing a much higher forest cover than the present one.…”
Section: Study Area and Experimental Designmentioning
confidence: 99%
“…As Dalle et al (2002) and Svenning et al (2004) remarked, some palm species may be associated with disturbances that occurred more than 20 years ago. In this sense, a climatic reconstruction of central Argentina not only observed the presence of silicophytolith of the Arecaceae family but also registered a peak of higher aridity and warm climate experimented 1,600 years ago (Giorgis et al 2015). These climatic conditions might have allowed that T. campestris reached the southernmost distribution in central Argentina.…”
Section: Vegetation Types and Environmental Factorsmentioning
confidence: 88%
“…These results are essential to develop adequate conservation strategies and useful for the sustainable management of this endangered species. It is accepted that the current distribution of palms is limited by climatic conditions prevailing during the cold season (Walther 2002), and that under warming scenarios some palm species may be extending their ranges into higher latitudes and altitudes (Walther et al 2007;Giorgis et al 2015). However, to our knowledge, there is no information about the behavior that T. campestris may show under changing scenarios of temperature and rainfall neither about its regeneration niche.…”
Section: Conclusion and Further Perspectivesmentioning
confidence: 99%